Characterization of research on disability in Colombia 2005-2012 (2013)
Background. Research on disability in Colombia has had isolated and poorly articulated developments, as well as a poor socialization of its results, which hinders the social appropriation and the spreading of knowledge. Objective. To characterize the research production on disability in the country between 2005 and 2012. Materials and methods. A web application was designed to register concluded investigations. This allowed the analysis of the main investigation research topics, methodological approaches, sources of funding, ways to socialize results, units and actors who produce knowledge, among other categories. Results. It has been found an increased interest in studying the topic in disciplines different from the traditionally related to disability and rehabilitation. It is highlighted the participation of disabled people as investigators. Conclusion. The country needs to strengthen the development of skills to produce, use and manage scientific knowledge in disability as a reference when political decisions are being made.